Exercise training to increase tumour natural killer‐cell infiltration in men with localised prostate cancer: a randomised controlled trial. (18th July 2022) - Djurhuus, Sissal Sigmundsdóttir; Simonsen, Casper; Toft, Birgitte Grønkær; Thomsen, Simon Nørskov; Wielsøe, Sabrina; Røder, Martin Andreas; Hasselager, Thomas; Østergren, Peter Busch; Jakobsen, Henrik; Pedersen, Bente Klarlund; Hojman, Pernille; Brasso, Klaus; et al.
Abstract : Objectives: To explore the effects of preoperative high‐intensity interval training (HIIT) compared to usual care on tumour natural killer (NK)‐cell infiltration in men with localised prostate cancer (PCa), as NK‐cell infiltration has been proposed as one of the key mechanisms whereby exercise can modulate human tumours. Patients and Methods: A total of 30 patients with localised PCa undergoing radical prostatectomy (RP) were randomised (2:1) to either preoperative aerobic HIIT four‐times weekly (EX; n = 20) or usual care (CON; n = 10) from time of inclusion until scheduled surgery. Tumour NK‐cell infiltration was assessed by immunohistochemistry (CD56 + ) in diagnostic core needle biopsies and corresponding prostatic tissue from the RP. Changes in cardiorespiratory fitness, body composition, blood biochemistry, and health‐related quality of life were also evaluated. Results: The change in tumour NK‐cell infiltration did not differ between the EX and CON groups (between‐group difference: −0.09 cells/mm 2, 95% confidence interval [CI] –1.85 to 1.66; P = 0.913) in the intention‐to‐treat analysis. The total number of exercise sessions varied considerably from four to 30 sessions. The per‐protocol analysis showed a significant increase in tumour NK‐cell infiltration of 1.60 cells/mm 2 (95% CI 0.59 to 2.62; P = 0.004) in the EX group. Further, the total number of training sessions was positively correlated with the change in NK‐cell infiltration ( r = 0.526, P = 0.021), peak oxygen uptake ( r = 0.514, P = 0.035) and peak power output ( r = 0.506, P = 0.038). Conclusion: Preoperative HIIT did not result in between‐group differences in tumour NK‐cell infiltration. Per‐protocol and exploratory analyses demonstrate an enhanced NK‐cell infiltration in PCa. Future studies are needed to test the capability of exercise to increase tumour immune cell infiltration.